2020
DOI: 10.1155/2020/2032359
|View full text |Cite
|
Sign up to set email alerts
|

Photoaging Skin Therapy with PRP and ADSC: A Comparative Study

Abstract: Background. Stem cells from adipose tissue (ADSCs) and platelet-rich plasma (PRP) are innovative modalities that arise due to their regenerative potential. Objective. The aim of this study was to characterize possible histological changes induced by PRP and ADSC therapies in photoaged skin. Methods. A prospective randomized study involving 20 healthy individuals, showing skin aging. They underwent two therapeutic protocols (protocol 1: PRP; protocol 2: ADSCs). Biopsies were obtained before and after treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 108 publications
(138 reference statements)
0
15
0
Order By: Relevance
“…To investigate fibrosis, a possible unwanted side‐effect of PRP in the skin, [ 20,21 ] and most specifically the potential transition of fibroblasts towards a myofibroblastic phenotype, we seeded human dermal fibroblasts (HdF) on GelMA scaffolds with and without TGF‐β1 (an inducer of myofibroblastic phenotype), as well as on our PRP‐GelMA scaffolds. Cultures on PRP‐GelMA scaffolds were not supplemented with FBS or recombinant growth factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate fibrosis, a possible unwanted side‐effect of PRP in the skin, [ 20,21 ] and most specifically the potential transition of fibroblasts towards a myofibroblastic phenotype, we seeded human dermal fibroblasts (HdF) on GelMA scaffolds with and without TGF‐β1 (an inducer of myofibroblastic phenotype), as well as on our PRP‐GelMA scaffolds. Cultures on PRP‐GelMA scaffolds were not supplemented with FBS or recombinant growth factors.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that PRP may induce fibrosis in skin [ 20,21 ] and other tissues, such as skeletal muscle. [ 56 ] Our findings show otherwise, as we did not observe the induction of fibrosis in any of the aforementioned studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 85 , 86 However, PRP may also cause skin erythema, inflammation and fibrosis, which indirectly accelerates ageing process in some cases and sometimes exerts ineffective effect on skin ageing. 86 , 87 , 88 Such defects may be due to the remain of heterologous activators and cell residuals (WBC and RBC) in PRP. In this study, the lysis and purification processes in hPL preparation not only released high concentrations of growth factors with no need of heterologous activators, but also removed cell residuals completely, thereby overcoming the defects of PRP.…”
Section: Discussionmentioning
confidence: 99%
“…CAL is regarded as a promising tool in the field of skin regenerative medicine and ASCs are attributed various beneficial effects in skin-based therapies, eg, amelioration of photoaging, wound healing, and skin diseases like atopic dermatitis. 138-140 However, a few studies addressed the relationship between ASCs and the various skin cancer types although CAL is readily applied in areas susceptible to skin cancer formation.…”
Section: Asc-mediated Effects On Skin Cancermentioning
confidence: 99%